2022
DOI: 10.3389/fnut.2022.908534
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omic Analyses Reveal Bifidogenic Effect and Metabolomic Shifts in Healthy Human Cohort Supplemented With a Prebiotic Dietary Fiber Blend

Abstract: Dietary fiber, a nutrient derived mainly from whole grains, vegetables, fruits, and legumes, is known to confer a number of health benefits, yet most Americans consume less than half of the daily recommended amount. Convenience and affordability are key factors determining the ability of individuals to incorporate fiber-rich foods into their diet, and many Americans struggle to access, afford, and prepare foods rich in fiber. The objective of this clinical study was to test the changes in microbial community c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 135 publications
(155 reference statements)
2
5
0
Order By: Relevance
“…Similar to other studies investigating gut microbiota changes in humans from prebiotic fibres, we observed a bifidogenic effect [ 55 , 56 , 90 , 130 , 134 , 135 , 136 ], in combination with an increase in Lachnospiraceae [ 98 , 137 ]. B. adolescentis appears to respond selectively to inulin [ 28 , 90 , 130 , 138 , 139 , 140 , 141 ] and resistant starch [ 37 , 98 , 134 , 142 , 143 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies investigating gut microbiota changes in humans from prebiotic fibres, we observed a bifidogenic effect [ 55 , 56 , 90 , 130 , 134 , 135 , 136 ], in combination with an increase in Lachnospiraceae [ 98 , 137 ]. B. adolescentis appears to respond selectively to inulin [ 28 , 90 , 130 , 138 , 139 , 140 , 141 ] and resistant starch [ 37 , 98 , 134 , 142 , 143 ].…”
Section: Discussionsupporting
confidence: 89%
“…Many of these microbes perform essential roles such as producing metabolites crucial for immune function, maintaining gut barrier integrity, and modulating circulating endotoxins [120]. Despite these efforts, endotoxins can still make their way into the circulation [121]. A recent study sheds light on how intestinally derived HDL helps manage these endotoxins [122].…”
Section: Intestinally Derived Hdlmentioning
confidence: 99%
“…They also found that higher fiber intake was associated with higher levels of indolepropionate, and lower levels of indolelactate and indoxyl sulfate. As a support, one recent intervention study found that a prebiotic fiber supplement could significantly increase plasma indolepropionate concentrations compared to the placebo among healthy young participants consuming a diet low in fiber ( Kang et al, 2022 ). Higher intakes of vegetables, fruits, whole grains, nuts, and legumes, and lower intakes of refined grains and red meat were associated with higher serum indolepropionate levels ( Qi et al, 2022 ).…”
Section: Microbial Metabolites Provide Functional Connection Between ...mentioning
confidence: 99%